Cardiorespiratory and metabolic determinants during moderate and high resistance exercise intensities until exhaustion using dynamic leg press: comparison with critical load - V.M. Arakelian; C.L. Goulart; R.G. Mendes; F.C. Caruso; V. Baldissera; R. Arena; A. Borghi-Silva (Brazilian Journal of Medical and Biological Research, 2018)
The objective of this study was to assess cardiovascular, respiratory, and metabolic responses during a commonly used dynamic leg press resistance exercise until exhaustion (TEx) at different intensities and compare with critical load (CL). This was a prospective, cross-sectional, controlled, and crossover study. Twelve healthy young men (23±2.5 years old) participated. The subjects carried out three bouts of resistance exercise in different percentages of 1 repetition maximum (60, 75, and 90% 1RM) until TEx. CL was obtained by means of hyperbolic model and linearization of the load-duration function. During all bout intensities, oxygen uptake (VO2), carbon dioxide production (VCO2), ventilation (VE), and respiratory exchange ratio (RER) were obtained. Variations (peak-rest=Δ) were corrected by TEx. In addition, systolic and diastolic blood pressure (SBP and DBP), blood lactate concentration [La-] and Borg scores were obtained at the peak and corrected to TEx. CL induced greater TEx as well as number of repetitions when compared to all intensities (P<0.001). During CL, Borg/TEx, ΔSBP/TEx, ΔDBP/TEx, and [La-] were significantly lower compared with 90% load (P<0.0001). In addition, VO2, VCO2, VE, and RER were higher during CL when compared to 90 or 75%. TEx was significantly correlated with VO2 on CL (r=0.73, P<0.05). These findings support the theory that CL constitutes the intensity that can be maintained for a very long time, provoking greater metabolic and ventilatory demand and lower cardiovascular and fatigue symptoms during resistance exercise.